Running on the treadmill: Practitioner experiences of mass supervision - Cracknell, Matt (European journal of probation, 2022)
This article explores the impacts that the addition of individuals serving short sentences has had on daily practice and working culture for probation workers. These practitioner perspectives are explored through the lens of ‘mass supervision’, providing a new insight into the harms and implications for its inherent deskilling qualities and constraints. This empirical research underlines three main themes related to the harms caused by mass supervision: firstly, that it inhibits innovative practice; secondly, that it necessitates a more limited model of supervision that undermines practitioner autonomy and the reach and scope of the supervisory relationship; and thirdly, that mass supervision corrodes the values of probation staff, leaving many experienced practitioners struggling ethically, practically and emotionally. The experience of mass supervision is compared to a treadmill by several practitioners and employed as a metaphor to analyse practice in the confines of mass supervision as generic, monotonous and relentless.